Innovations and Inequalities in Digital Taxation: Lessons from Global Experiences - Qoriah, Desi (Summa : Journal of Accounting and Tax, 2024)
The rapid expansion of the digital economy has pressured traditional tax systems, demanding reforms to address profit shifting, base erosion, and fair allocation of taxing rights. This narrative review examines the effectiveness, equity, and policy implications of digital tax reforms at global, national, and regional levels. Literature was systematically collected from Scopus, Web of Science, and Google Scholar, focusing on digital taxation, reform policies, compliance, and the OECD two-pillar framework. Findings reveal mixed outcomes. OECD/G20 initiatives promote cooperation but often favor developed economies, limiting benefits for developing nations. At the national level, reforms show varied impacts: Indonesia improved small-enterprise compliance, while Ghana’s electronic levy exposed regressive risks. Comparative evidence indicates advanced economies with robust infrastructures achieve higher compliance and revenues, while developing countries face institutional and capacity challenges. Innovations in tax administration—digital registration, cloud systems, and AI—have enhanced efficiency and collection, though concerns about equity and long-term sustainability remain. Broader systemic factors, including corruption, governance, and institutional capacity, critically shape reform success. The review concludes that effective digital tax reforms must balance efficiency with distributive justice, align with development goals, and strengthen evidence through interdisciplinary and quantitative approaches. Addressing these challenges is essential to ensuring the equitable sharing of digitalization’s benefits across economies.